Análisis financiero de los activos de la empresa Colbapi S.A. y su representación en la rentabilidad - Camposano Díaz, Victoria Noemi (2019)
This work was carried out with the purpose that financial analysis is not only an evaluation tool, but also a tool that allows us to make better decisions for the company, with the purpose of improving quality standards to have a better posture. In the market, these standards will guide the company to a new perspective or a new era where customers are satisfied with their purchases and the company improving the attention and products provided in a better quality and presentation